Rare haematogenous sarcoma metastasis to the heart in a child. (2nd October 2019) - Gross, Gil J.; Postovsky, Sergey; Khoury, Asaad
Abstract: Haematogenous non-contiguous metastatic spread of remote solid tumours to the heart is rare. We describe a previously healthy 5-year-old girl who presented with extensive intracardiac involvement by metastatic pelvic sarcoma.